2016
DOI: 10.1016/j.talanta.2016.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent blood lipid analysis by means of near infrared spectroscopy, in geese

Abstract: a b s t r a c tThis study provides accurate near infrared (NIR) spectroscopic models on some laboratory determined clinicochemical parameters (i.e. total lipid (5.57 71.95 g/l), triglyceride (2.59 71.36 mmol/l), total cholesterol (3.81 7 0.68 mmol/l), high density lipoprotein (HDL) cholesterol (2.45 70.58 mmol/l)) of blood serum samples of fattened geese. To increase the performance of multivariate chemometrics, samples significantly deviating from the regression models implying laboratory error were excluded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…It has been shown that spectroscopy in the mid-IR range can serve as an alternative basis for the clinical measurement of urea and glucose in blood serum [ 25 ]. The literature reports promising results on important serum parameters such as urea, total protein, albumin, triglycerides or total cholesterol [ 26 , 27 , 28 , 29 ]. Nevertheless, the possibility of simultaneous determination of several blood parameters has not been studied enough.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that spectroscopy in the mid-IR range can serve as an alternative basis for the clinical measurement of urea and glucose in blood serum [ 25 ]. The literature reports promising results on important serum parameters such as urea, total protein, albumin, triglycerides or total cholesterol [ 26 , 27 , 28 , 29 ]. Nevertheless, the possibility of simultaneous determination of several blood parameters has not been studied enough.…”
Section: Discussionmentioning
confidence: 99%
“…This previously reported NIR bile analysis scheme has potential for clinical on-site analysis due to the simple and rapid analysis that requires no pretreatment of raw bile. Other than the analysis of bile, NIR spectroscopy has been extensively adopted for biomedical diagnosis 2,3 using relevant biological specimens including blood, 4,5 serum, [6][7][8] saliva, 9 and tissue, 10,11 and diverse chemometric and deep learning methods such as partial least squares (PLS), [5][6][7][8]12 linear discriminant analysis (LDA), 3,11,14 support vector machine (SVM), 13 and artificial neural network (ANN) 13 are combined for multivariate analysis of acquired NIR spectra.…”
Section: Introductionmentioning
confidence: 99%
“…And nowadays, NIR spectroscopy has been widely studied and applied for measuring biochemical parameters. Bazar et al utilized NIR spectroscopy to predict total lipids, triglycerides, total cholesterol and high-density lipoprotein cholesterol in goose serum samples, and the correlation coefficients of prediction ( R P ) were 0.864, 0.966, 0.850 and 0.793, respectively [ 29 ]. Filho et al applied the NIR spectroscopy to determine the triglyceride level in human plasma.…”
Section: Introductionmentioning
confidence: 99%